Wolbachia effects in natural populations of Chorthippus parallelus from the Pyrenean hybrid zone. (13th May 2014) - Zabal‐Aguirre, M.; Arroyo, F.; García‐Hurtado, J.; de la Torre, J.; Hewitt, G. M.; Bella, J. L.
Abstract We evaluate for the first time the effect of Wolbachia infection, involving two different supergroups, on the structure and dynamics of the hybrid zone between two subspecies of Chorthippus parallelus (Orthoptera) in the Pyrenees. Wolbachia infection showed no effects on female fecundity or a slight increment in females infected by F supergroup, although in the last case it has to be well established. Cytoplasmic incompatibility (CI) is confirmed in crosses carried out in the field between individuals from a natural hybrid population. This CI, registered as the relative reduction in embryo production (sh), was of sh = 0.355 and sh = 0.286 in unidirectional crosses involving B and F supergroups, respectively. CI also occurred in bidirectional crosses (sh = 0.147) but with a weaker intensity. The transmission rates of the two Wolbachia strains (B and F) were estimated by the optimization of a theoretical model to reach the infection frequencies observed in certain population. To fit this scenario, both supergroups should present transmission rates close to 1. Further, we have simulated the infection dynamics, and hence, the capacity of Wolbachia to structure the population of the host insects and to affect to reproduction and genetic introgression in the hybrid zone. This represents a first example of the influence of Wolbachia in an insect natural hybrid zone.